A Survey on Human T-cell Lymphotropic Virus Type 1 (HTLV-1) and Xenotropic Murine Leukemia Virus-Related Virus (XMRV) Coinfection in Tehran, Iran - Keshavarz, Mohsen (J Pharm Bioallied Sci, 2018)
BACKGROUND: Xenotropic murine leukemia virus-related virus (XMRV) is a gamma retrovirus, which has been detected in patients with prostate cancer, chronic fatigue syndrome, and general population with a number of acquired infections such as infection with human T-cell lymphotropic virus (HTLV) and human immunodeficiency virus (HIV). The aim of this study was to determine the HTLV-1 and XMRV coinfection for the first time in Iranian patients who were admitted to the Tehran hospitals. MATERIALS AND METHODS: Two hundred and ninety one patients suspected with HTLV-1 were referred to the hospitals affiliated to the Iran University of Medical Sciences, Tehran, Iran from April 2012 to October 2016. Genomic deoxyribonucleic acid (DNA)/ribonucleic acid (RNA) from peripheral blood mononuclear cells/cerebrospinal fluids was extracted by High Pure Viral Nucleic Acid Kit (Roche, Germany). After complementary DNA synthesis, conventional reverse transcriptase polymerase chain reaction was used for the detection of HTLV-1 or XMRV-infected patients. Statistical Package for Social Sciences (SPSS) software, version 16 (SPSS, Chicago, IL, USA) was used for statistical analyses. RESULTS: Of the 291 patients suspected of HTLV infection, 123 (42.3%) were male with a mean age of 38±15 years. HTLV-1 RNA was found in 93 (31.9%) specimens comprising 40 men (41.3%) and 53 women (56.9%). Of the 93 patients who were HTLV-1 positive, one sample (1%) was positive for XMRV env gene. CONCLUSION: These findings suggest that the lack of significant detection of XMRV in patients who were HTLV-1 positive could not be associated with complications of HTLV-1. Although this is a preliminary report from Iranian patients with HTLV-1, further studies are needed to show the actual prevalence of XMRV infection by geographical distribution and various populations.